Visitor Engagement contribution to increasing Revisit Intention of Borobudur Temple tourists - Gusdinar Dwi Putra; Yadi Ernawadi (Fakultas Ekonomi Universitas Dehasen Bengkulu, 2023)
The purpose of this study was to examine the effect of the visitor engagement on revisit intention mediated by Candi Borobudur's memorable tourism experiances in Magelang Regency. The instrument used in this study has passed the external validity test, construct validity test, instrument validity test using product moment, and reliability test. The instrument is used as a means of collecting data from respondents, namely domestic tourists with a minimum age of 17 years who have experience visiting tourist destinations which are the objects assessed in this study as many as 121 people. The data collection technique used is cross-sectional or one shot study. The data analysis technique used is multiple linear regression using SPSS version 25 and using the sobel test. Of the ten proposed research hypotheses, seven of them are supported by empirical data. The findings of this study indicate that memorable tourism experiences cannot mediate the effect of visitor engagement on revisit intention. Meanwhile the use of other concepts to directly influence revisit intention can be proposed by further researchers. The results of this study are also useful for the management of the object being assessed and similar tourism industries regarding the design of strategies that are relevant to improving the quality of these attributes.